Comparison of Nitroaromatic Compounds Metabolites Types by Sequencing Performance of Anaerobic-Aerobic and Aerobic-Anaerobic Processes - Fahimeh Teimouri; Mohammad Mehdi Amin; Mohsen Sadani; Bijan Bina; Hossein Khanahmad (Journal of Environmental Health and Sustainable Development, 2022)
Introduction: Xenobiotic contamination is a global concern. Nitroaromatic compounds enter the environment through ammunition, ordnance disposal, burning the outdoors, and leakage of ammunition. Thirty percent of explosives enter the environment without any change, which can cause pollution of soil, water, and health concerns. So, effective remediation of the contaminated area is necessary. Materials and Methods: Soil bioreactors consisted of plastic pans placed in larger pans. Explosives were analyzed using a High-Performance Liquid Chromatography (HPLC) system, Model 486 UV detector, and a Nova Pak C18 guard column. LC-MS detected intermediates on an RP18 analytical column equipped with a C18 guard column. Results: Rhamnolipid significantly affected 2,4,6-trinitrotoluene (TNT) and Pentaerythritol tetranitrate (PETN) biodegradation rates with the help of indigenous bioaugmentation. The mentioned condition was also effective on the maximum bacterial growth in various nitroaromatics (S0) concentrations, in which the top change occurred. The specific growth rate was foremost in a setup containing microbial inoculated and biosurfactant (0.19) responding to 800 mg/kg TNT and 150 mg/kg PETN. The maximum bacterial enumeration of sludge and biosurfactant were 4.8 × 108 and 4.1 × 108 CFU/g, respectively. The aerobic-anaerobic sequence could be able to produce less harmful metabolites. In an aerobic-anaerobic sequence process, using the anaerobic process could help complete the azo compounds degradation in the aerobic stage. Conclusion: Aerobic-anaerobic condition is suitable for bioremediation contaminated explosive sites and achieving complete mineralization. Generally, this proposed method is possible for in situ bioremediation.